The normative framework of the protection of personal data in the field of (bio)medicine - Rajić Nataša (Temida)
This paper discusses the normative framework of regulating the right to protection of personal data relating to biomedical treatment procedures of patients as human rights. The subjects of analysis are the European Convention, the Convention on Human Rights and Biomedicine and the relevant provisions of the Constitution of the Republic of Serbia. The right to protection of personal data in the field of biomedicine is analyzed comparatively in terms of the content of this right and in terms of basis for limiting this right. The analysis is carried out to find answers to the question if the constitutional framework is consistent in terms of exercising this right, taking into account the constitutional provision on the direct application of human rights guaranteed by international treaties and other provisions that determine the status of international sources of law in our legal system. [Projekat Ministarstva nauke Republike Srbije, br. 179079: Zaštita životne sredine, biomedicina i pravo]